Cross sectional study to investigate the influence of treatment regimes on the development of haemophilic arthropathy - Hilberg, T.; Czepa, D. (Hämostaseologie, 2009)
Haemophilic arthropathy is often present in patients with severe haemophilia. New studies demonstrate that only a small amount and a short exposure of blood in vitro are able to induce an impairment of the joint cartilage. Free blood in the joint leads to different mechanisms and includes cartilage and bone damage induced by a release of macrophages and monocytes followed by activated cytokines and inflammatory processes. Another mechanism is mediated by free iron resulting in synovitis and synovial hyperplasia and a neoangiogenesis on the base of VEGF release is common. At worst, these processes result in a complete picture of haemophilic arthropathy reducing quality of life. Few studies are available about the influence of factor treatment regime, e. g. prophylaxis or on-demand therapy, on the development of haemophilic arthropathy. However these studies investigated in most cases children. Therefore, it is still impossible to give recommendations for the right treatment in adult haemophilic patients because data are still lacking. For that reason, we attempt to initiate the HemArthro-Project to investigate the influence of treatment therapy on the development of arthropathy in adult haemophilic patients. This study includes the investigation of functional musculoskeletal parameters for the description of joint function in maximal 500 severe haemophilic patients parted into two groups of treatment regime (prophylaxis vs. on-demand). The investigators are seeking further assistance from the haemophilic treatment centers for the support of this study.
Keywords: Arthropathy; prophylaxis; demand; joint